Computer-mediated interdisciplinary teams: theory and reality. - Vroman K; Kovacich J (Journal of Interprofessional Care, 2002)
The benefit of experience, tempered with the wisdom of hindsight and 5 years of text-based, asynchronous, computer-mediated, interdisciplinary team communications, provides the energy, insights and data shared in this article. Through the theoretical lens of group dynamics and the epistemology of interdisciplinary teaming, we analyze the interactions of a virtual interdisciplinary team to provide an understanding and appreciation of collaborative interdisciplinary communication in the context of interactive technologies. Whilst interactive technologies may require new patterns of language similar to that of learning a foreign language, what is communicated in the interdisciplinary team process does not change. Most important is the recognition that virtual teams, similar to their face-to-face counterparts, undergo the same challenges of interdisciplinary teaming and group developmental processes of formation: forming, storming, norming, performing, and transforming. After examining these dynamics of communication and collaboration in the context of the virtual team, the article concludes with guidelines facilitating interdisciplinary team computer-mediated communication.